Local application of low level laser therapy in mice ameliorates ovarian damage induced by cyclophosphamide. (1st July 2021) - Oubiña, Gonzalo; Pascuali, Natalia; Scotti, Leopoldina; Bianchi, Silvia; May, María; Martínez, Jorge Esteban; Marchese Ragona, Clariana; Higuera, Javier; Abramovich, Dalhia; Parborell, Fernanda
Abstract: The aim of the present study is to assess whether low level laser therapy (LLLT) can protect ovaries from chemotherapy-induced gonadotoxicity using a mice model of premature ovarian failure induced by cyclophosphamide (CTX). LLLT (64 J/cm 2 ) increased the number of antral follicles whilst decreasing the number of atretic follicles compared to CTX alone. LLLT increased the number of primordial follicles compared with those in the CTX group but they did not differ from those in the control group. LLLT treatment increased the number of AMH-positive follicles compared to CTX alone. LLLT application increased ovarian weight, serum progesterone concentration and P450scc protein levels compared to CTX alone. LLLT reduced the apoptosis in antral follicles and the BAX/BCL-2 ratio compared to CTX alone. Vascular morphology, analysed by CD31 and α-SMA immunostaining, was restored in LLLT-treated ovaries compared to CTX alone. In conclusion, application of LLLT prior to CTX might serve as a promising and novel protocol to preserve female fertility in cancer survivors. Highlights: Cyclophosphamide is one of the most gonadotoxic alkylating agents. Low Level Laser Therapy can decrease inflammation and induce tissue regeneration. Photobiomodulation ameliorates cyclophosphamide-induced ovarian damage in mice. Low Level Laser Therapy is a candidate to preserve fertility in cancer survivors.